Deciphering the Structural and Functional Paradigms of Clostridioides difficile Toxins TcdA and TcdB - Mohammad Qutub; Amol Tatode; Ujban Md Hussain; Tanvi Premchandani; Jayshree Taksande; Milind Umekar; Deepak Thakre (Bacteria)
Clostridioides difficile Infection (CDI) continues to be a major cause of antibiotic-associated diarrhea and pseudomembranous colitis, fueled in large measure by virulence factors TcdA and TcdB. These giant glucosyltransferase toxins interfere with host cytoskeletal integrity and inflammatory signaling by inhibiting Rho GTPase; however, the detailed structural dynamics, receptor selectivity, and subcellular trafficking mechanisms remain in part unspecified. This review integrates recent insights from cryo-electron microscopy (cryo-EM) and X-ray crystallography to describe the quaternary architecture of TcdA/B, emphasizing conformational changes key to pore formation and endosomal escape. We also examine the genomic heterogeneity of hypervirulent C. difficile strains (e.g., ribotype 027), correlating toxin gene polymorphisms (e.g., tcdC mutations) with increased toxin production and virulence. Mechanistic explanations of toxin-driven inflammasome activation and epithelial barrier dysfunction are situated within host immune evasion mechanisms, including microbiota-derived bile acid regulation of toxin stability. Subsequent innovative therapeutic strategies, encompassing the utilization of engineered neutralizing antibodies that specifically target the autoprocessing domain alongside structure-guided small-molecule inhibitors, are subjected to a rigorous evaluation. By integrating structural biology, systems-level omics, and clinical epidemiology, this review establishes a comprehensive framework for understanding C. difficile toxin pathogenesis and guiding next-generation precision antimicrobials.